УТИЦАЈ БРЗИНЕ ПРОТОКА ВАЗДУХА НА ШИРЕЊЕ ПОЖАРА У ОБЈЕКТУ - THE INFLUENCE OF AIR FLOW SPEED ON FIRE PROPAGATION IN OBJECT - Jevtić, Radoje Branislav (Arhitektura i urbanizam, 2015)
Fire presents the process of the uncontrolled combustion that makes material damage and endangers human lives. It is important to know the factors that fire depends on for success projecting and realization of fire protection systems. One of such factors is different air flow that could be presented as wind, draft and the like. The simulation of different air flow speeds and its influences on fire propagation in object were analyzed in this paper.